HEALTH STATUS OF THE LODHA COMMUNITY IN WEST BENGAL (International Journal of Food and Nutritional Sciences, 2024)
Globally, it is often acknowledged that “health is wealth.” That most people’s health is largely influenced by their financial situation—without money, access to healthcare is practically unachievable—is, nevertheless, never highlighted. Food consumption, influenced by availability and purchasing capacity, is largely responsible for the population’s health and nutritional status. The Lodha Tribal community is one of the Particularly Vulnerable Tribal Groups in West Bengal. They live mainly in Jhargram and Paschim Medinipur District of West Bengal. The study result shows that per day dietary intake of the Lodha tribal groups is less than the Recommended Dietary Allowance (RDA), affecting their health status.